The Influence of Organized Activeness on the Cumulative Achievement Index of Students of the Accounting Education Study Program, Faculty of Economics, Makassar State University - Ernawati Ernawati; M. Ridwan Tikollah; Sahade Sahade (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of organizational activity on the cumulative achievement index of students in the Accounting Education Study Program, Faculty of Economics, Makassar State University. The variables in this study are organizational activity as the independent variable and the cumulative achievement index as the dependent variable. The population in this study were students of the Accounting Education Study Program, Faculty of Economics, Makassar State University. The sampling technique used was proportionate stratified random sampling; a sample from the population was selected randomly and proportionally with a sample of 80 students. The techniques used for data collection are questionnaires and documentation. The data analysis techniques used are descriptive percentage analysis, instrument testing consisting of validity and reliability testing, hypothesis testing consisting of simple linear regression analysis, a t-test, and coefficient of determination using SPSS version 25 for Windows. Based on the results of the data analysis that has been carried out, the simple linear regression equation model Y = 2,929 + 0.009 X means that for each additional unit of organizational activity, the cumulative achievement index has increased by 0.009. Meanwhile, from the analysis of the coefficient of determination (r2), the value of r2 = 0.173 means that the effect of organizational activity on the cumulative achievement index is 17.3% and the remaining 82.7% is influenced by other factors. Meanwhile, the results of the test-test analysis obtained a significant value of 0.000 <0.05, which means that organizational activity has a significant effect on the cumulative achievement index, thus the hypothesis is accepted.